2021
DOI: 10.2174/1573407216999200507122039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant and Antimicrobial Activity of Ziziphora clinopodiodes Essential Oil Eluted at Different Times

Abstract: Objective: Ziziphora clinopodioides is an edible medicinal plant belongs to the Labiatae family that widespread all over Iran. It used as culinary and also in cold and cough treatments in Iran. The aim of present work was to evaluate the effect of different timeframes during the hydrodistillation on essential oil composition, antimicrobial and antioxidant activity. Materials and Methods: The essential oil of Z. clinopodiodes was extracted via hydrodistillation with Clevenger apparatus. The fractions of essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Damani et al (2022) reported antioxidant properties for pulegone and stated that EOs containing pulegone are an appropriate alternative for application in food instead of synthetic preservations. In addition, excellent antioxidant and antimicrobial effects of isomenthone have been reported (Alizadeh et al, 2021). Joshi et al (2022) also reported significant antimicrobial properties of 1,8‐cineole against S. aureus , E. coli , and Salmonella typhymurium .…”
Section: Resultsmentioning
confidence: 99%
“…Damani et al (2022) reported antioxidant properties for pulegone and stated that EOs containing pulegone are an appropriate alternative for application in food instead of synthetic preservations. In addition, excellent antioxidant and antimicrobial effects of isomenthone have been reported (Alizadeh et al, 2021). Joshi et al (2022) also reported significant antimicrobial properties of 1,8‐cineole against S. aureus , E. coli , and Salmonella typhymurium .…”
Section: Resultsmentioning
confidence: 99%